2012
DOI: 10.1371/journal.pone.0043250
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Does Not Protect against MPTP-Induced Neurotoxicity in BDNF Happloinsufficent Mice

Abstract: Exercise has been demonstrated to potently protect substantia nigra pars compacta (SN) dopaminergic neurons from 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced neurotoxicity. One mechanism proposed to account for this neuroprotection is the upregulation of neurotrophic factors. Several neurotrophic factors, including Brain Derived Neurotrophic Factor (BDNF), have been shown to upregulate in response to exercise. In order to determine if exercise-induced neuroprotection is dependent upon BDNF, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 133 publications
1
22
0
Order By: Relevance
“…Autonomic dysfunction in these mice is ameliorated by ADF and exacerbated by excessive caloric intake 150 . Enhancing neurotrophic support (BDNF and glial-cell-line-derived neurotrophic factor), induction of protein chaperones, ketogenesis and ghrelin signalling are among the neuroprotective mechanisms of action of IMS suggested from the experiments with PD animal models 151153 .…”
Section: Ims and Neurological Disordersmentioning
confidence: 99%
“…Autonomic dysfunction in these mice is ameliorated by ADF and exacerbated by excessive caloric intake 150 . Enhancing neurotrophic support (BDNF and glial-cell-line-derived neurotrophic factor), induction of protein chaperones, ketogenesis and ghrelin signalling are among the neuroprotective mechanisms of action of IMS suggested from the experiments with PD animal models 151153 .…”
Section: Ims and Neurological Disordersmentioning
confidence: 99%
“…The mechanisms by which exercise induces upregulation of D2/ D3 receptors have been investigated in animal models of striatal dopaminergic injury, modeling Parkinson's disease physiology. In rodents, wheel running after stimulant exposure produces significant changes in gene transcription factors capable of modulating dopaminergic neurotransmission in the mesolimbic pathways (Greenwood et al, 2011;Zlebnik et al, 2014), and wheel running attenuates MPTPinduced damage to dopaminergic cells in wild-type mice, but not in BDNF (+/ − ) knockdown mice (Gerecke et al, 2012). Similarly, BDNF receptor antagonists blocked the effects of treadmill running against damage to dopaminergic neurons, as indicated by preserved levels of tyrosine hydroxlase activity, in a rat model of Parkinson's disease using striatal injection of 6-hydroxydopamine (Real et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported improvement in motor function, along with the preservation of DA neurons and the restoration of dopaminergic terminals, using tyrosine hydroxylase (TH) immunostaining, within the striatum. In these toxin models, neuroprotection has been principally attributed to an exercise-induced increase of neurotrophic factors such as brain-derived neurotrophic factor (BDNF) or glial-derived neurotrophic factor (GDNF) 7881 . An alternative mechanism for neuroprotection of these models may be though the exercise induced down regulation of DAT, the primary uptake system for 6-OHDA and MPTP 73, 75 .…”
Section: Exercise and Parkinson’s Diseasementioning
confidence: 99%